Teaching entrepreneurship students the practice of innovation: A brain-based guided experience approach - Ronald Jean Degen (Revista de Ciências da Administração : RCA)
This paper presents a new method for teaching entrepreneurship students to practice innovation and to create high-impact business opportunities.  The teaching method is based on the guided experience learning model that was developed by Caine et al. (2009) to develop the executive functions in the brains of learners, and on the innovation framework that was introduced by Verganti (2009).  The cognitive perspective of creativity, as explained by Weisberg (2006), is used to show how the practice of innovation can be learned.  The model used for the creative process is based on research by Wallas (1926), and on recent neurological findings on the deliberate and spontaneous pathways to creativity (Carson, 2010).  The concept of effectual process (SARASVATHY, 2008) provides an approach to the validation of the students’ radical innovation ideas.